High-strength chemical-corrosion-resistant heat-aging-resistant heat-conducting silica gel and preparation method thereof

By combining modified chemically resistant and heat-resistant benzene-type polysiloxane with glass fiber cloth to form a three-dimensional cross-linked network, the strength and chemical resistance problems of thermally conductive silicone are solved, and the thermal conductivity and mechanical properties are improved.

CN121316341APending Publication Date: 2026-01-13SHENZHEN YIZE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511542245.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-27
Publication Date
2026-01-13

AI Technical Summary

Technical Problem

Existing thermally conductive silicone has problems such as insufficient flexibility, easy puncture, fragility, and poor chemical corrosion resistance in electronic products, new energy, and 5G cabinet base station fields. In addition, the addition of high filler content leads to thermal stress concentration, which affects the thermal conductivity.

Method used

Thermally conductive silicone substrates were prepared by blending modified chemically resistant and heat-resistant benzene-type polysiloxane, tackifier, modified filler, crosslinking agent and platinum catalyst, and then calendered and cured on glass fiber cloth to form a three-dimensional crosslinked network, which combined with glass fiber to enhance thermal conductivity and chemical corrosion resistance.

Benefits of technology

The strength, puncture resistance, chemical acid and alkali corrosion resistance, and heat aging resistance of thermally conductive silicone have been improved, ensuring that it maintains excellent thermal conductivity and mechanical properties at high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121316341A_ABST
    Figure CN121316341A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of heat-conducting silica gel and discloses high-strength heat-conducting silica gel resistant to chemical corrosion and heat aging and a preparation method of the high-strength heat-conducting silica gel resistant to chemical corrosion and heat aging. Comprising the following components in parts by weight: 100 parts of modified chemical corrosion-resistant heat-aging-resistant benzene type polysiloxane, 1.5-3 parts of a tackifier, 63-100 parts of a modified filler, 0.034-0.61 part of an inhibitor, 0.067-1.02 part of a platinum catalyst and 0.5-0.9 part of a cross-linking agent, benzene type polysiloxane is used as a main chain, a rigid benzene ring inhibits high-temperature conformation change, phonon loss is reduced, and an efficient heat conduction channel is constructed through a three-dimensional cross-linked network and pi-pi accumulation; the glass fiber enhances the mechanical property and the puncture resistance; fluorine atoms improve chemical corrosion resistance, and a free radical trapping agent improves heat aging resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of thermally conductive silicone technology, specifically to a high-strength, chemically resistant, and heat-aging resistant thermally conductive silicone and its preparation method. Background Technology

[0002] Thermally conductive silicone is a thermally conductive material composed of organic silicone and various thermally conductive fillers and additives. It possesses excellent high and low temperature resistance, electrical insulation, weather resistance, and thermal conductivity, making it a commonly used polymer material for heat dissipation in electronic products. Researchers often focus on improving thermal conductivity, but have overlooked the inherent limitations of thermally conductive silicone in its application. Its good flexibility leads to a series of problems during use. In the field of electronic products, during SMT (Surface Mount Technology) automatic bonding, ordinary thermally conductive silicone can easily puncture solder joints on circuit boards. In the new energy field, ordinary thermally conductive silicone on battery packs can burn through instantly when exposed to acid or alkali sprays. In the field of 5G base station cabinets, the weight of the products easily crushes ordinary thermally conductive silicone. In response, the industry currently typically increases the strength of thermally conductive silicone by increasing its hardness, but this cannot significantly increase its fracture strength and puncture resistance. In addition, the molecular chains are highly flexible and are prone to violent vibrations at high temperatures, which dissipates the energy of phonons and reduces the thermal conductivity of the silicone. This is often addressed by adding a large amount of thermally conductive filler to restrict chain movement and improve thermal conductivity. However, a high filler content will inevitably lead to agglomeration and thermal stress concentration, damaging the molecular chain structure. Summary of the Invention

[0003] To overcome the shortcomings of the existing technology, this invention provides a high-strength, chemically resistant, and heat-aging resistant thermally conductive silicone. This high-strength, chemically resistant, and heat-aging resistant thermally conductive silicone is prepared by blending modified chemically resistant and heat-aging resistant benzene-type polysiloxane, tackifier, modified filler, inhibitor, crosslinking agent, and platinum catalyst to prepare a thermally conductive silicone substrate, which is then calendered onto glass fiber cloth and cured in an oven. Specifically, benzene-type siloxane is selected as the main chain of the thermally conductive silicone. The planar rigid benzene ring side chains with high steric hindrance suppress the disordered conformational changes of the molecules at high temperatures, reducing phonon transmission loss. The π-π stacking of the benzene rings can form high crystallinity, reducing voids and constructing efficient thermally conductive channels. Trifunctional phenyl-tris(dimethylsiloxane)silane, as a crosslinking agent, can form a three-dimensional crosslinked network, synergistically forming a thermally conductive network that runs through the entire structure, improving thermal conductivity. Glass fiber, whose main component is silicon dioxide, has good compatibility with the thermally conductive silicone and can be easily... The thermally conductive silicone is well dispersed and embedded in a three-dimensional cross-linked network, increasing its strength while avoiding stress concentration. The glass fiber cloth attached to the surface of the thermally conductive silicone enhances its stress resistance and puncture resistance. Chemically inert fluorine atoms are introduced into the benzene-type siloxane backbone and work synergistically with silicon nitride to improve the thermally conductive silicone's resistance to spraying and chemical acid and alkali corrosion. In addition, the introduced 2-acrylate-2-(4-benzoyl-3-hydroxyphenoxy)ethyl ester can absorb free radicals, reducing the decomposition effect of free radicals on the molecular chain during heat transfer and improving its heat aging resistance.

[0004] The purpose of this invention is to provide a high-strength, chemically resistant, heat-resistant, and thermally conductive silicone rubber and its preparation method.

[0005] This invention is achieved through the following technical solution: A high-strength, chemically resistant, heat-resistant, and aging-resistant thermally conductive silicone is provided. The silicone is made by laminating glass fiber cloth onto the surface of a thermally conductive silicone substrate. The thermally conductive silicone substrate, by weight, comprises the following components: 100 parts of modified chemically resistant, heat-resistant, and aging-resistant benzene-type polysiloxane; 1.5-3 parts of tackifier; 63-100 parts of modified filler; 0.034-0.61 parts of inhibitor; 0.067-1.02 parts of platinum catalyst; and 0.5-0.9 parts of crosslinking agent. The modified chemically resistant, heat-resistant, and aging-resistant benzene-type polysiloxane is prepared by reacting the chlorine atom of the modified chemically resistant, heat-resistant, and aging-resistant agent with the hydroxyl group of a hydroxyl-terminated diphenyl-dimethyl (siloxane and polysiloxane). The structural formula of the modified chemically resistant, heat-resistant, and aging-resistant agent is shown in Formula 1.

[0006] In one specific embodiment, the modified filler comprises 45-60 parts of alumina, 15-30 parts of silicon nitride, and 3-10 parts of glass fiber, and is surface-treated with 0.5-1.5 wt% of γ-glycidoxypropyltrimethoxysilane.

[0007] In one specific embodiment, the tackifier is hydroxyl silicone oil; In one specific embodiment, the inhibitor is ethynylcyclohexanol; In one specific embodiment, the platinum catalyst is a Karstedt catalyst; In one specific embodiment, the crosslinking agent is phenyl-tris(dimethylsiloxane)silane; In one specific embodiment, the fiberglass cloth is type E with a thickness of 0.085±0.007 mm.

[0008] In one specific embodiment, the preparation of the modified chemical corrosion resistant and heat aging resistant agent includes the following steps: Under nitrogen atmosphere, 2-acrylate-2-(4-benzoyl-3-hydroxyphenoxy)ethyl ester and an amine catalyst were dissolved in anhydrous dichloromethane; a solution of (3,3,3-trifluoropropyl)dichloromethylsilane dissolved in a small amount of anhydrous dichloromethane was added dropwise over 30-40 minutes, and the mixture was stirred at 0 °C for 1-1.5 hours; the mixture was then stirred at room temperature for 4-6 hours, filtered, concentrated, and purified by column chromatography to obtain the modified chemical corrosion resistant and heat aging resistant agent.

[0009] In one specific embodiment, the amount of 2-acrylate-2-(4-benzoyl-3-hydroxyphenoxy)ethyl ester is 0.95-1 times the molar amount of (3,3,3-trifluoropropyl)dichloromethylsilane; the amine catalyst is triethylamine, and the amount is 1.1-1.2 times the molar amount of (3,3,3-trifluoropropyl)dichloromethylsilane.

[0010] In one specific embodiment, the preparation of the modified chemically resistant and heat-resistant benzene-type polysiloxane includes the following steps: Under nitrogen atmosphere, hydroxyl-terminated diphenyl-dimethyl (siloxane and polysiloxane) is dissolved in anhydrous toluene, and a modified chemical corrosion resistant and heat aging resistant agent is added; an amine catalyst is added dropwise, and the mixture is stirred at 50-60 °C for 8-12 hours; the mixture is cooled, filtered, and the filtrate is concentrated to obtain modified chemical corrosion resistant and heat aging resistant benzene-type polysiloxane.

[0011] In one specific embodiment, the amount of the modified chemical corrosion resistant and heat aging resistant agent is 2.05-2.1 times the molar amount of hydroxyl-terminated diphenyl-dimethyl (siloxane and polysiloxane); the amine catalyst is one of triethylamine and N,N-diisopropylethylamine, and the amount is 2.1-2.2 times the molar amount of hydroxyl-terminated diphenyl-dimethyl (siloxane and polysiloxane).

[0012] Another objective of this invention is to protect a method for preparing a high-strength, chemically resistant, heat-resistant, and thermally conductive silicone rubber, comprising the following steps: 1) Add the modified chemically resistant and heat-resistant benzene-type polysiloxane to a planetary mixer with a speed of 300-400 rpm, add the thickener, and mix for 10-30 minutes; add the modified filler in three batches, and mix under vacuum to -0.1 to -0.09 MPa for 15-35 minutes; add the inhibitor and stir for 3-7 minutes, discharge the material and store it under nitrogen to obtain component A; 2) Add the crosslinking agent and platinum catalyst to a planetary mixer and mix for 3-5 minutes at room temperature, under vacuum, and at a speed of 300-400 rpm. Discharge the mixture and seal it with nitrogen to obtain component B. 3) Install the fiberglass cloth on the unwinding machine, pass it through the flattening roller, and then pass it through the ion wind zone at a speed of 0.5-1 m / min for surface electrostatic treatment until the surface static voltage is ≤50 V; place it in a sealed dust-free temporary storage chamber for later use; 4) Place component A and component B in a static mixer at a mass ratio of 1:1 and mix at 400-500 rpm for 20-40 s to obtain a thermally conductive adhesive substrate. Preheat the three rollers of the calender to 60-80 ℃, set the roller speed to 3-4 m / min, and transfer the thermally conductive adhesive substrate between the front and middle rollers of the calender head through the feed hopper. Calender the substrate under a pressure of 5-10 MPa to form a thermally conductive adhesive film with a thickness of 0.3-1 mm. Then, press it tightly with the glass fiber cloth placed between the middle and rear rollers. Feed the film into a tunnel oven and bake it in three sections at 145 ℃, 125 ℃, and 115 ℃ at a speed of 3-4 m / min until it is fully bonded to obtain a high-strength, chemically resistant, and heat-resistant thermally conductive silicone. Beneficial effects

[0013] This invention provides a high-strength, chemically resistant, and heat-aging resistant thermally conductive silicone. The high-strength, chemically resistant, and heat-aging resistant thermally conductive silicone is prepared by blending modified chemically resistant and heat-aging resistant benzene-type polysiloxane, tackifier, modified filler, inhibitor, crosslinking agent, and platinum catalyst to prepare a thermally conductive silicone substrate, which is then calendered onto glass fiber cloth and cured in an oven. Specifically, benzene-type siloxane is selected as the main chain of the thermally conductive silicone. The planar rigid benzene ring side chains with high steric hindrance suppress the disordered conformational changes of the molecules at high temperatures, reducing phonon transmission losses. The π-π stacking of the benzene rings can form high crystallinity, reducing voids and constructing efficient thermally conductive channels. Trifunctional phenyl-tris(dimethylsiloxane)silane, as a crosslinking agent, can form a three-dimensional crosslinked network, which, together with the highly thermally conductive silicon nitride filler, forms a thermally conductive network that runs through the entire structure, giving it excellent thermal conductivity. The main component of glass fiber is silicon dioxide, which has good compatibility with the thermally conductive silicone. The fiberglass cloth, which is well dispersed and embedded in the three-dimensional cross-linked network, and is attached to the surface of the thermally conductive silicone to increase the strength of the silicone while avoiding stress concentration, thus enhancing the stress resistance and puncture resistance of the silicone. Chemically inert fluorine atoms are introduced into the benzene-type siloxane backbone and work with silicon nitride to improve the thermally conductive silicone's resistance to spraying and chemical acid and alkali corrosion. In addition, the introduced 2-acrylate-2-(4-benzoyl-3-hydroxyphenoxy)ethyl ester can absorb free radicals, reduce the decomposition effect of free radicals on the molecular chain during heat transfer, and improve the heat aging resistance. Attached Figure Description

[0014] Figure 1 This describes the synthesis route of the modified chemical corrosion resistant and heat aging resistant agent in Example 1; Figure 2 The nuclear magnetic resonance hydrogen spectrum of the modified chemical corrosion resistant and heat aging resistant agent of Example 1. Detailed Implementation

[0015] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0016] Unless otherwise specified, the experimental methods used in the embodiments are conventional methods, and the materials and reagents used are commercially available unless otherwise specified.

[0017] The raw materials used in the examples and comparative examples are described below: Hydroxyl-terminated diphenyl-dimethyl (siloxane and polysiloxane): 5000 mPa.s, purchased from Shanghai Maclean Biochemical Technology Co., Ltd. 2-Acrylate-2-(4-benzoyl-3-hydroxyphenoxy)ethyl ester: 98%, purchased from Shanghai Maclean Biochemical Technology Co., Ltd. (3,3,3-trifluoropropyl)dichloromethylsilane: 98%, purchased from Shanghai Maclean Biochemical Technology Co., Ltd.; Amine catalyst 1: Triethylamine (TEA), ≥99.5%, purchased from Shanghai Maclean Biochemical Technology Co., Ltd.; Amine catalyst 2: N,N-diisopropylethylamine (DIPEA), 99%, purchased from Shanghai Maclean Biochemical Technology Co., Ltd. Crosslinking agent: Phenylacetyl-tris(dimethylsiloxane)silane, 97%, Shanghai Haohong Biomedical Technology Co., Ltd.; Platinum catalyst: Karstedt catalyst, Pt content 2%, purchased from Shanghai Maclean Biochemical Technology Co., Ltd. Inhibitor: Ethynylcyclohexanol, 99%, purchased from Shanghai Maclean Biochemical Technology Co., Ltd.; Tackifier: Hydroxy silicone oil, hydroxyl content 8 wt%, purchased from Wuhan Jiyesheng Chemical Co., Ltd. Glass fiber: ECS-307™ alkali-free chopped strands, purchased from China Jushi Co., Ltd.; Fiberglass cloth: Type E, product specification 2116, thickness 0.085±0.007 mm, purchased from China Jushi Co., Ltd. Alumina: D50 of 45 μm, purchased from Shanghai Maclean Biochemical Technology Co., Ltd.; Silicon nitride, 200 nm, purchased from Shanghai Maclean Biochemical Technology Co., Ltd. Silane coupling agent: γ-glycidoxypropyltrimethoxysilane (A-187), 97%, purchased from Shanghai Maclean Biochemical Technology Co., Ltd. Modified chemical corrosion resistant and heat aging resistant agent: self-made, preparation method is as follows: Under nitrogen atmosphere, dry 2-acrylate-2-(4-benzoyl-3-hydroxyphenoxy)ethyl ester (0.98 molar equivalent) and triethylamine (1.2 molar equivalent) were dissolved in anhydrous dichloromethane and stirred for 10 minutes. Over 30 minutes, a solution of (3,3,3-trifluoropropyl)dichloromethylsilane (1 molar equivalent) dissolved in a small amount of anhydrous dichloromethane was added dropwise. The mixture was cooled to below 0 °C and stirred for 1.5 hours. The reaction was then brought to room temperature and stirred for 5 hours until the reaction was complete. The mixture was filtered, the filtrate was concentrated, and purified by column chromatography to obtain a modified chemical corrosion resistant and heat-resistant aging agent with a yield of 93.2%.

[0018] Modified benzene-type polysiloxane resistant to chemical corrosion and heat aging: self-made, preparation method as follows: Under nitrogen atmosphere, dry hydroxyl-terminated diphenyl-dimethyl (siloxane and polysiloxane) (1 molar equivalent) was dissolved in anhydrous toluene and stirred until dissolved; dry modified chemical corrosion resistant and heat aging resistant agent (2.05 molar equivalent) was added; N,N-diisopropylethylamine (2.1 molar equivalent) was slowly added dropwise, and the temperature was raised to 60 °C and stirred for 10 hours until the reaction was complete; the mixture was cooled, filtered, and the filtrate was concentrated to obtain modified chemical corrosion resistant and heat aging resistant benzene-type polysiloxane.

[0019] Modified chemical corrosion resistant and heat aging resistant methyl polysiloxane: self-made. The preparation method is different from that of modified chemical corrosion resistant and heat aging phenyl polysiloxane in that the hydroxyl-terminated diphenyl-dimethyl (siloxane and polysiloxane) is replaced with hydroxyl-terminated polydimethylsiloxane.

[0020] Modified benzene-type polysiloxane: self-made, preparation method is as follows: Dry hydroxyl-terminated diphenyl-dimethyl (siloxane and polysiloxane) and 1-vinyl-1,1,3,3-tetramethyldisiloxane were stirred and mixed at room temperature for 10-15 minutes, with a molar ratio of silane to silanol of 2.1:1. Dibutyltin dilaurate (0.03 wt% of the total amount) was slowly added dropwise, and stirring was continued for 20 minutes. The temperature was slowly raised to 100 °C, and the reaction was stirred for 5 hours until no bubbles were generated, at which point the reaction was complete. After cooling, modified benzene-type polysiloxane was obtained.

[0021] Modified fillers: γ-glycidoxypropyltrimethoxysilane was mixed with anhydrous ethanol and water, and the pH was adjusted to 4-5 with acetic acid. The mixture was hydrolyzed for 30 minutes to obtain a coupling agent hydrolysate. Alumina, silicon nitride and glass fiber were added to a mixer in sequence, and the prepared coupling agent hydrolysate was sprayed in. The mixture was mixed at 700 rpm and 55 ℃ for 1 hour. The mixture was then transferred to an oven at 110 ℃ and dried for 3 hours to obtain the modified filler.

[0022] Unless otherwise specified, all components and raw materials used in the embodiments and comparative examples of this invention are commercially available, and the same type of components and raw materials are used in each parallel experiment.

[0023] Examples and Comparative Examples A high-strength, chemically resistant, heat-resistant, and thermally conductive silicone rubber, the weight proportions of which are shown in Table 1, is prepared as follows: 1) Add the modified chemically resistant and heat-resistant benzene-type polysiloxane to a planetary mixer at 300 rpm, add the thickener, and mix for 20 minutes; add the modified filler in three batches, and mix under vacuum to -0.09 MPa for 30 minutes; add the inhibitor and stir for 5 minutes, discharge the material and store it under nitrogen to obtain component A; 2) Add the crosslinking agent and platinum catalyst to a planetary mixer and mix under vacuum at room temperature for 5 minutes. Discharge the mixture and seal it with nitrogen to obtain component B. 3) Install the fiberglass cloth on the unwinding machine, pass it through the flattening roller, and then pass it through the ion wind zone at a speed of 0.5 m / min for surface electrostatic treatment until the surface static voltage is ≤50 V; place it in a sealed dust-free temporary storage chamber for later use; 4) Component A and component B are placed in a static mixer at a mass ratio of 1:1 and mixed at 400 rpm for 30 s to obtain a thermally conductive adhesive substrate. The three rollers of the calender are preheated to 65 ℃, and the roller speed is set to 3 m / min. The thermally conductive adhesive substrate is transferred through the feed hopper between the front and middle rollers of the calender head and calendered under a pressure of 8 MPa to form a thermally conductive film with a thickness of 1 mm. It is then pressed tightly with the glass fiber cloth placed between the middle and rear rollers. It is then fed into a tunnel oven and cured at a speed of 3-4 m / min through three ovens at 145 ℃, three ovens at 125 ℃, and three ovens at 115 ℃ until it is fully bonded, thus obtaining a high-strength, chemically resistant, and heat-resistant thermally conductive silicone.

[0024] Table 1 High-strength, chemically resistant, heat-resistant, and thermally conductive silicone (parts by weight)

[0025] The high-strength, chemically resistant, heat-resistant, and thermally conductive silicone prepared in the examples and comparative examples were subjected to the following performance tests, and the results are shown in the attached figures and Table 2, respectively.

[0026] 1H NMR spectroscopy: The synthesized modified chemical corrosion resistant and heat aging resistant agent sample was dissolved in deuterated dimethyl sulfoxide to prepare a 1.0 wt% solution. The NMR spectrum of the sample was measured using a 1H NMR spectrometer at 400 MHz. The results are as follows. Figure 2 As shown, the integral number is consistent with the hydrogen number of the modified chemical corrosion resistant and UV resistant agent, and the chemical shift is consistent with its chemical environment, indicating that the target product has been synthesized.

[0027] Tensile strength and elongation at break: A universal testing machine was used to test the tensile strength and tensile properties of the thermally conductive silicone. The two ends of the thermally conductive silicone were neatly clamped on the tensile testing machine, the tensile speed was set to 50 mm / min, and the stress-strain curves were recorded in real time until the silicone broke.

[0028] Thermal conductivity test: The thermal conductivity of the thermally conductive silicone samples was tested according to ASTM D5470 standard using a TPS2200 thermal constant analyzer from HotDiSk, Sweden.

[0029] Puncture resistance: According to ASTM F1306 standard, using a 1 mm diameter steel needle, the steel needle was pressed against the heat-conducting silicone at a moving speed of 50 mm / min, and the maximum force value when the steel needle penetrated the material was recorded.

[0030] Chemical corrosion resistance: The thermally conductive silicone was placed in 10% dilute hydrochloric acid and 4% sodium hydroxide solution respectively, and immersed at 35 ℃ for 30 minutes. The tensile strength retention rate was then measured.

[0031] Heat aging resistance: After the thermally conductive silicone is aged at 125 ℃ for 1000 hours, the rate of decrease in thermal conductivity is calculated.

[0032] Compression set: According to ASTM D395, the thermally conductive silicone sample was installed in the fixture and compressed to 25%. The test conditions were 150 °C and 50% humidity for 22 hours. After that, the thermally conductive silicone sample was removed and the fixture was loosened. After standing at room temperature for one hour, the height was measured and the measurement data was recorded.

[0033] Table 2 Performance test results of high-strength, chemically resistant, heat-resistant, and thermally conductive silicone rubber.

[0034] As shown in Table 2, the high-strength, chemically resistant, and heat-resistant thermally conductive silicone prepared in Examples 1-4 possesses excellent mechanical properties. Increasing the amount of tackifier and glass fiber can improve the hardness and strength of the material to a certain extent, thereby enhancing the tensile strength and puncture resistance of the thermally conductive silicone. Simultaneously, the use of benzene-type siloxane and the addition of glass fiber to construct a structurally stable, high-strength cross-linked network can effectively disperse stress, avoiding stress concentration and deformation. Furthermore, it can recover through chain segment movement after the removal of external force, thus achieving a low compression set rate.

[0035] Comparative Examples 1 and 2 show that introducing fluorine atoms into the thermally conductive silicone can effectively improve its resistance to chemical acid and alkali corrosion. This is because the CF bond is inert and forms a dense and stable electron cloud around the carbon chain. Simultaneously, its synergistic electron-withdrawing properties reduce the polarity of the molecular chain, promoting its chemical inertness. Based on the principle of like compatibility, the low-polarity molecular chain is less likely to be wetted or penetrated by polar acid and alkali solutions, thus achieving resistance to chemical acid and alkali corrosion. In Comparative Example 3, silicon nitride was replaced with alumina with a larger particle size, and in Comparative Example 4, no glass fiber was added, which is not conducive to the formation of a dense cross-linked structure and makes it easier for acid and alkali solutions to penetrate.

[0036] Comparative examples and Comparative Example 1 show that using benzene-type polysiloxane as the thermally conductive silicone substrate results in a higher thermal conductivity. This is because benzene-type polysiloxane has good chain regularity, and the sterically hindered phenyl side chains impede molecular chain movement, which helps to improve crystallinity and reduce phonon energy dissipation caused by molecular chain movement, thus improving thermal conductivity. Furthermore, the synergistic effect of silicon nitride and glass fiber forms a dense cross-linked network structure, which facilitates phonon propagation, thereby improving thermal conductivity.

[0037] The introduction of 2-acrylate-2-(4-benzoyl-3-hydroxyphenoxy)ethyl ester, an anti-UV functional component, can effectively absorb free radicals generated during thermal aging, preventing chain decomposition and thus improving the heat aging resistance of thermally conductive silicone. As shown in Examples and Comparative Example 1, the rigid benzene rings in the side chains of benzene-type polysiloxanes exhibit strong chemical stability and high steric hindrance, reducing the intensity of thermal motion and minimizing aging caused by the transmission of chain free radicals. Therefore, their heat aging resistance is superior to that of methyl-type polysiloxanes.

[0038] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.

Claims

1. A high-strength, chemical corrosion resistant, heat-aging resistant, heat-conductive silica gel, characterized in that, The glass fiber cloth is made by bonding glass fiber cloth on the surface of the heat-conducting silica gel base material, and the heat-conducting silica gel base material comprises the following components in parts by weight: modified chemical corrosion and heat aging resistant benzene type polysiloxane 100 parts, tackifier 1.5-3 parts, modified filler 63-100 parts, inhibitor 0.034-0.61 parts, platinum catalyst 0.067-1.02 parts, and crosslinking agent 0.5-0.9 parts. Formula 1.

2. The high-strength, chemically resistant, heat-aging resistant, thermally conductive silicone gel of claim 1, wherein, The tackifier is hydroxyl silicone oil; the inhibitor is ethynylcyclohexanol; the platinum catalyst is Karstedt catalyst; the crosslinking agent is phenyl-tris(dimethylsiloxane)silane; and the glass fiber cloth is E type, with a thickness of 0.085±0.007 mm.

3. The high-strength, chemically resistant, heat-aging resistant, thermally conductive silicone of claim 1, wherein, The modified filler comprises alumina 45-60 parts, silicon nitride 15-30 parts, and glass fiber 3-10 parts, and is surface treated by 0.5-1.5wt% of γ-glycidoxypropyltrimethoxysilane based on the total filler content.

4. The high-strength, chemically resistant, heat-aging resistant, thermally conductive silicone of claim 1, wherein, The preparation of the modified chemical corrosion and heat aging resistant agent comprises the following steps: Under the condition of nitrogen, 2-acrylic acid-2-(4-benzoyl-3-hydroxyphenoxy) ethyl ester and amine catalyst are dissolved in anhydrous dichloromethane; (3,3,3-trifluoropropyl) dichloromethylsilane solution dissolved in a small amount of anhydrous dichloromethane is added dropwise within 30-40 minutes, and stirring is performed at 0 ℃ for 1-1.5 hours; stirring is performed at room temperature for 4-6 hours, and the modified chemical corrosion and heat aging resistant agent is obtained by filtering, concentrating the filtrate, and column chromatography purification.

5. The high-strength, chemically resistant, heat-aging resistant, thermally conductive silicone of claim 4, wherein, The amount of 2-acrylic acid-2-(4-benzoyl-3-hydroxyphenoxy) ethyl ester is 0.95-1 times the molar amount of (3,3,3-trifluoropropyl) dichloromethylsilane; and the amount of amine catalyst is 1.1-1.2 times the molar amount of (3,3,3-trifluoropropyl) dichloromethylsilane.

6. The high-strength, chemically resistant, heat-aging resistant, thermally conductive silicone of claim 1, wherein, The preparation of the modified chemical corrosion and heat aging resistant benzene type polysiloxane comprises the following steps: Under the condition of nitrogen, hydroxyl-terminated diphenyl-dimethyl(siloxane and polysiloxane) is dissolved in anhydrous toluene, and the modified chemical corrosion and heat aging resistant agent is added; amine catalyst is added dropwise, and stirring is performed at 50-60 ℃ for 8-12 hours; the modified chemical corrosion and heat aging resistant benzene type polysiloxane is obtained by cooling, filtering, and concentrating the filtrate.

7. The high-strength, chemically resistant, heat-aging resistant, thermally conductive silicone of claim 6, wherein, The amount of modified chemical corrosion and heat aging resistant agent is 2.05-2.1 times the molar amount of hydroxyl-terminated diphenyl-dimethyl(siloxane and polysiloxane); and the amount of amine catalyst is 2.1-2.2 times the molar amount of hydroxyl-terminated diphenyl-dimethyl(siloxane and polysiloxane).

8. The preparation method of a high-strength, chemically resistant, heat-resistant, and thermally conductive silicone rubber as described in claim 1, characterized in that, The preparation comprises the following steps: 1) Add the modified chemical corrosion resistant and heat aging resistant phenyl polysiloxane to a planetary mixer with a rotation speed of 300-400 rpm, add the tackifier, mix for 10-30 minutes; add the modified filler in three times, vacuum to -0.1--0.09 MPa, mix for 15-35 minutes; add the inhibitor and stir for 3-7 minutes, discharge and store in nitrogen; obtain component A; 2) Add the crosslinking agent and platinum catalyst to the planetary mixer and mix at room temperature, vacuum, 300-400 rpm rotation speed for 3-5 minutes, discharge and store in nitrogen; obtain component B; 3) Install the glass fiber cloth on a unwinder, pass through a flattening roller, then pass through an ion wind area at a speed of 0.5-1 m / min for surface electrostatic treatment until the surface electrostatic voltage is ≤50 V; place in a closed dust-free temporary storage bin for use; 4) Place component A and component B in a static mixer at a mass ratio of 1:1, mix at a rotation speed of 400-500 rpm for 20-40 s to obtain a heat conducting adhesive base material; preheat the three roller cylinders of the calender to 60-80 ℃, set the roller rotation speed to 3-4 m / min, transfer the heat conducting adhesive base material through the feed hopper between the front roller and the middle roller of the calender head, calender at a pressure of 5-10 MPa to obtain a heat conducting adhesive film with a thickness of 0.3-1 mm; then extrude and tightly bond with the glass fiber cloth placed between the middle roller and the rear roller; send into a tunnel furnace with three ovens at 145 ℃, three ovens at 125 ℃, and three ovens at 115 ℃, and cure at a speed of 3-4 m / min until completely bonded to obtain a high-strength chemical corrosion resistant and heat aging resistant heat conducting silicone.